2014
DOI: 10.1016/j.bjorl.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hearing protection used by police officers in the shooting range

Abstract: The findings showed high levels of sound pressure in the shooting range, which exceeded the maximum recommended noise (120 dBC), even when measured through the insertion microphone. Therefore, alternatives to improve the performance of hearing protection should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 11 publications
(22 reference statements)
0
7
0
14
Order By: Relevance
“…According to Guida et al (2014), noise is the main physical causative agent of Noise-Induced Hearing Loss (NIHL). NIHL also causes stress and impair an effective communication at work, leading to work related accidents (Leão & Dias, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…According to Guida et al (2014), noise is the main physical causative agent of Noise-Induced Hearing Loss (NIHL). NIHL also causes stress and impair an effective communication at work, leading to work related accidents (Leão & Dias, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The discharge of firearms constitutes a major source of routine noise among police officers during the course of their work shift. In a recent study of police officers in Brazil, Guida et al (2014) reported noise levels that exceeded the national occupational health standards.…”
Section: Introductionmentioning
confidence: 99%
“…Firearms are a common source of noise and hazardous noise levels associated with NIHL commonly occurs in the military and the police force during activities that involve firearm and pulse-induced explosions (Sulkowski et al 2017). A number of studies have reported abnormal levels of noise exposures in various occupations, including construction workers, farmers, railway workers, civil aviation workers, military personnel, firefighters, shipyard workers, offshore workers, healthcare workers, musicians, and police officers (Guida et al 2014, Win et al 2015. Previously published studies of hazardous noise exposures have focused on conventional occupations such as airport grounds staff and military personnel, while only a few studies have targeted less obvious professions such as police officers (Lesage et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A modern silencer of the firearm is vastly superior to ear-level protection and the only available form of suppression capable of making certain sporting arms safe for hearing [1][2][3][4][5][6][7][8]. Forces show an increasing number of cases of hearing damage [9][10][11][12][13][14][15]. Many of the early developments of the silencer were mainly empirical in nature [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%